MEG3 activates necroptosis in human neuron xenografts modeling Alzheimer’s disease - Balusu, Sriram; Horré, Katrien; Thrupp, Nicola; Craessaerts, Katleen; Snellinx, An; Serneels, Lutgarde; T’Syen, Dries; Chrysidou, Iordana; Arranz, Amaia M.; Sierksma, Annerieke; Simrén, Joel; Karikari, Thomas K.; et al. (Science (American Association for the Advancement of Science), 2023)
Neuronal cell loss is a defining feature of Alzheimer’s disease (AD), but the underlying mechanisms remain unclear. We xenografted human or mouse neurons into the brain of a mouse model of AD. Only human neurons displayed tangles, Gallyas silver staining, granulovacuolar neurodegeneration (GVD), phosphorylated tau blood biomarkers, and considerable neuronal cell loss. The long noncoding RNA MEG3 was strongly up-regulated in human neurons . This neuron-specific long noncoding RNA is also up-regulated in AD patients. MEG3 expression alone was sufficient to induce necroptosis in human neurons in vitro. Down-regulation of MEG3 and inhibition of necroptosis using pharmacological or genetic manipulation of receptor-interacting protein kinase 1 (RIPK1), RIPK3, or mixed lineage kinase domain-like protein (MLKL) rescued neuronal cell loss in xenografted human neurons. This model suggests potential therapeutic approaches for AD and reveals a human-specific vulnerability to AD. Neurons are one of the longest-living and enduring cell types of the human body. Balusu et al . xenografted human neurons into mouse brains containing amyloid plaques (see the Perspective by Sirkis and Yokoyama). The human neurons, but not the mouse neurons, displayed severe Alzheimer’s pathology, including tangles and necroptosis. Human neurons up-regulated the neuron-specific maternally expressed gene 3 (MEG3) in response to amyloid plaques. Down-regulation of MEG3 protected the neurons from dying in the xenograft model of Alzheimer’s disease. Downstream of MEG3, genetic or pharmacological manipulation of signaling kinases in the necroptosis pathway also protected neurons, suggesting a potential lead toward therapeutic approaches for Alzheimer’s disease. —Stella M. Hurtley In models of Alzheimer’s disease, a long noncoding RNA activates necroptosis and necroptosis inhibition rescues neuronal loss.